Computational biology and environmental sciences - Liu, Limin Angela, 1974-; Wei, Dongqing; Li, Yixue, 1955-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book presents cutting-edge research in the field of computational and systems biology, presenting studies ranging from the atomic/molecular level to the genomic level and covering a wide spectrum of important biological problems and applications"--Provided by publisher.
25. Root water uptake model of Populus euphratica in desert riparian forest in extreme arid region / Yongzheng Tian ... [et al.] -- 26. The fuzzy integrated energy prior-warning model based on entropy weight / Yaqun He ... [et al.] -- 27. A novel flowsheet for the recycling of valuable constituents from waste printed circuit boards / Jingfeng He ... [et al.].
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed Dec. 7, 2010).
Keywords: Computational biology; Bioinformatics; Bioinformatics; Bionanotechnology; Computational biology; Computational bionanoscience; Environmental studies; Genomics; Metabolomics; Proteomics; Structure and molecular modeling; Systems biology; Electronic books